ANALYSIS AND EVALUATION OF THE QUALITY MANAGEMENT SYSTEM IN THE IMPLEMENTATION OF THE INTEGRATED MANAGEMENT SYSTEM - Попадинець, Ірина Романівна (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2021)
Based on the results of the analysis of theoretical and methodological principles of implementation of the integrated management system (ISM) at the enterprise, an algorithm for assessing product quality to ensure its competitiveness in the international market is proposed. One of the most widespead standards included in the ISM is the ISO 14000 series of standards, ie environmental management systems (EMS). Construction products must meet the requirements of current regulatory and technical documents (standards, specifications, etc.). Requirements for construction products are divided into general and specific. The general requirements of construction products include the quality of raw materials; compliance with the requirements of appearance; indicators of functional purpose; safety indicators; indicators of conformity of marking and packing. Specific requirements for construction products characterize the quality of specific types of construction materials. An effective method of assessing the quality of goods is the indicator "product rating". The concept of "product rating" is associated with the degree of superiority of one product, one model over others in those conditions in which the operation or use of the product by the consumer. This indicator reflects the organic combination of the technical level of the product, the quality of its manufacture and efficiency in operation. The rating is required to compare models of the same class, type or size. At the same time, with the help of this indicator it is possible to carry out a relative assessment of products of different classes, but identical in functional purpose. The rating is based on a systematic approach to the concept of product quality and its indicators. To carry out the diagnosis it is necessary to set a score and symbols for the tabular description: ++ (excellent) - 5; + (good) - 4; 0 (satisfactory) - 3; - (with shortcomings) - 2; - (with major shortcomings) - 1. Therefore, to determine the rating of the product it is necessary to make a differentiated assessment of individual quality indicators, the definition of which will give a general quantitative description of the advantages of one product over another. An effective method of researching product quality is consumer feedback, using sociometric research, namely questionnaires.